Future imaginaries of urban school reform - Jan Nespor (Arizona State University, 2016)
Drawing on analytic heuristics from critical discourse analysis and cultural political economy (Jessop, 2010; Wodak, 2002), this article examines the temporal premises and "futures" embedded in a report and reform proposal created in a mid-sized, American city, Columbus, Ohio, in 2013. The product of a city-wide commission appointed in response to a school 'cheating' scandal, the report is both a condensation of key premises and claims circulating through national education policy discourses, and an effort to fit those ideas to a particular urban locale. This fitting involves aligning the city with a particular neoliberal representation or "imaginary" of the future that pervades current education policy discourse and planning. The article unpacks the temporal premises associated with this imaginary and shows their influence on the city's planning. Among other things, the discourse individuates scholastic time and subordinates the present to a distant future that is represented as an already-known or predictable state of affairs. It positions practices such as standardized testing as temporal technologies for predicting the child's position in the imagined future, and reframes racially- and class-based inequalities as differences in the kinds of futures towards which groups are oriented. The effect is to overwrite political questions of what kind of future we might want to create with technical questions of how best to prepare for an inevitable future we can't avoid.